CMR of Ventricular Function. - Keenan NG; Pennell DJ (Echocardiography, 2007)
Cardiovascular magnetic resonance (CMR) is the reference standard for the assessment of ventricular dimensions, function, and mass in terms of accuracy and reproducibility. It has been thoroughly validated both ex vivo and against other imaging techniques. Measurements are highly accurate and no geometrical assumptions need to be made about the ventricle. A routine ventricular dataset of images can be acquired in less than 5 minutes and analyzed in about the same time. The field is rapidly advancing with increasing automation and simplification in both image acquisition and analysis. Using parallel and real time imaging techniques, good quality data can be obtained even in patients who are unable to hold their breath. While providing useful information in all patients with suspected heart failure, CMR should particularly be considered in those with poor echo windows, where it can also be combined with myocardial stress. Tagging techniques can provide highly detailed information about myocardial torsion and strain for individual myocardial segments. In a research environment, the very high degree of interscan reproducibility can dramatically reduce the number of patients needed to perform clinical trials.